Lactobacillus acidophilus supplementation in human subjects and their resistance to enterotoxigenic Escherichia coli infection. Issue 3 (12th August 2013) - Ouwehand, A. C.; ten Bruggencate, S. J. M.; Schonewille, A. J.; Alhoniemi, E.; Forssten, S. D.; Bovee-Oudenhoven, I. M. J.
Abstract : To assess the effect of Lactobacillus acidophilus (American Type Culture Collection (ATCC) 700396) on enterotoxigenic Escherichia coli (ETEC) infection, in the present study, a parallel, double-blind, placebo-controlled 4-week intervention was performed in healthy males. The subjects largely consumed their habitual diet, but had to abstain from consuming dairy foods generally high in Ca. The subjects were randomised into the L. acidophilus (dose 10 9 colony-forming units twice daily; n 20) or the placebo ( n 19) group. After an adaptation period of 2 weeks, the subjects were orally infected with a live, but attenuated, ETEC vaccine, able to induce mild, short-lived symptoms. Before and after the challenge, the subjects recorded stool consistency, bowel habits, and frequency and severity of gastrointestinal complaints. The ETEC challenge led to a significant increase in faecal output on the 2nd day and a concomitant increase in Bristol stool scale scores. Likewise, abdominal pain, bloating, flatulence, fever, headache and nausea peaked 1 d after the oral challenge. The concentrations of faecal calprotectin and IgA peaked 2 d after and that of serum IgM peaked 9 and 15 d after the oral challenge. The concentrations of serum IgA and IgG were unaffected. The ETEC challenge led to a reduction in the number of Bacteroides–Prevotella, Bifidobacterium, Clostridium cluster XIVab and total faecal bacteria. Probiotic treatment was associated with a larger increase in Bristol stool scale scores and more fever, headache and nausea after the ETEC challenge compared with the placebo treatment. These differences were, however, small and with substantial variation within the groups. Oral application of an attenuated live ETEC vaccine provides a useful model for food-borne infections. Supplementation with L. acidophilus ATCC 700396, however, was ineffective in reducing ETEC infection symptoms in healthy men.